Low-alkali and alkali-resistant cement and preparation method thereof
By using a wide range of low-alkali cement formulas and mixed hole-blocking materials, the problems of narrow sources of low-alkali cement raw materials are solved, which improves the durability and compactness of cement and reduces production costs.
Patent Information
- Application Number
- CN202411350079.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2024-12-27
AI Technical Summary
The source of low-alkali cement raw materials is relatively narrow, resulting in limited production and high cost, and the outflow of chemical salt solutions inside cement products leads to alkaline-panning phenomenon.
Using a low-alkali cement formula including limestone, riverbed peeling clay, sandstone, modified phosphogypsum, bauxite, coal gangue and mixed hole plugging materials. The mixed hole plugging materials are composed of modified plastic powder, gelatin powder and hole plugging agent. The hole plugging agent contains water-absorbing resin, rubber and metal ion sealing agent, which is used to reduce the efflux of alkaline substances and the formation of holes.
The source of low-alkali cement raw materials has been expanded, the outflow of alkaline substances has been reduced, the durability and compactness of cement has been improved, the alkaline phenomenon has been reduced, and the production cost has been reduced.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of low-alkali cement preparation, in particular to low-alkali alkali-resistant cement and a preparation method thereof. Background Art
[0002] The production process of cement plants in my country has been changed from "wet process" to "dry process", resulting in an increase in alkali content. With the increasing strength of concrete, the amount of cement will inevitably increase, and the alkali content will also increase. High-alkali cement has become an important factor inducing "alkali-aggregate reaction". In order to ensure the durability of concrete and avoid longitudinal cracking of concrete caused by "alkali-aggregate reaction" as much as possible, low-alkali cement should be used as much as possible, and the alkali content in cement should be limited.
[0003] At present, most low-alkali cements are made from low-alkali clinker, low-alkali gypsum, and some mineral admixtures (such as blast furnace slag, coal gangue, etc.) or acidic adjustment materials (such as phosphorus slag, sulfide or acidic ore, etc.), mainly to avoid excessive introduction of alkaline substances and reduce alkalinity. However, this kind of low-alkali cement has high requirements for low-alkali clinker, and the source of raw materials for low-alkali clinker is relatively narrow, mainly in the limestone raw materials and clay with low alkalinity, or it needs to be processed in the early stage to remove alkali, so the production volume of low-alkali cement is limited and the production cost remains high. In addition, although various grades of low-alkali cement appear on the market, after a period of use, the building surface, especially the wall surface in a high-humidity environment (such as toilets and kitchens), still has more or less alkali phenomenon. After observation, it is found that there are numerous air holes of various sizes on the cement wall surface. The chemical salt solution (such as calcium hydroxide, carbonate, etc.) inside the cement product reaches the wall surface along the air holes and forms white granular substances after drying. Summary of the invention
[0004] The purpose of the present invention is to provide a low-alkali alkali-resistant cement and a preparation method thereof, so as to solve the problem that the current low-alkali cement raw material source is relatively narrow, resulting in limited production and high production costs, and the chemical salt solution inside the cement product flows out to the surface to form efflorescence.
[0005] In order to solve the above technical problems, the present invention adopts the following technical solutions: A low-alkali alkali-resistant cement, comprising 700-800 parts of limestone, 100-150 parts of riverbed exfoliated clay, 80-100 parts of sandstone, 75-80 parts of modified phosphogypsum, 70-80 parts of bauxite, 60-70 parts of coal gangue, 50-70 parts of tailings, and 30-40 parts of mixed pore plugging materials; wherein; The mixed pore plugging material comprises 38-42% of modified plastic powder, 32-35% of gelatin powder and 25-28% of pore plugging agent.
[0006] A further technical solution is that the pore plugging agent is composed of 80-100 parts of water-absorbing resin, 50-55 parts of rubber, 40-45 parts of water-swellable polyurethane, 10-15 parts of a compatibilizer and 1-20 parts of a metal ion sealing agent.
[0007] A further technical solution is that the water-absorbing resin adopts a saponified copolymer with vinyl ether and olefin unsaturated carboxylic acid or its derivatives as main components, or a grafted polymer of polyvinyl alcohol / acrylate.
[0008] A further technical solution is that the rubber is a 1,3-diene rubber whose crystallization region or glass transition region at room temperature reaches 5% to 50%.
[0009] A further technical solution is that the water absorption rate of the water-absorbing resin is a medium swelling rate of 200% to 350%.
[0010] A further technical solution is that the particle size of the pore plugging agent is between 50 and 100 um.
[0011] A further technical solution is that the metal ion blocking agent is an aminocarboxylic acid derivative such as condensed phosphate or ethylenediaminetetraacetic acid and its metal salt.
[0012] A further technical solution is that 0.5 to 2 parts of an anti-metal corrosion agent are also added to the mixed gel material.
[0013] A further technical solution is that the compatibilizer is a hydrophilic and lipophilic multi-block copolymer of polyethylene oxide blocks.
[0014] A method for preparing low-alkali alkali-resistant cement comprises the following steps: S1, take: 750 parts of limestone, 120 parts of riverbed stripping clay, 90 parts of sandstone, 60 parts of tailings, crush, mix and put into kiln for calcination in sequence to obtain clinker; S2, 80 parts of modified phosphogypsum, 75 parts of bauxite, and 65 parts of coal gangue are crushed, mixed with the clinker in S1, and bagged to obtain a semi-finished product; S3. 40% of modified plastic powder, 33% of gelatin powder and 27% of pore plugging agent in 35 parts of mixed filling material are kneaded and crushed at low temperature, then sealed and packaged, and placed in bagged semi-finished products.
[0015] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects: The invention provides a low-alkali alkali-resistant cement and a preparation method thereof. The low-alkali alkali-resistant cement has a wide range of ingredients, and uses clay stripped from a riverbed to replace general clay, with less alkaline residue, and even some of the clay has a certain acidity; bauxite reduces the content of Na2O in cement, which is beneficial to reducing the alkali dissolution of the alkali skeleton in the cement and the alkali-silicon reaction of the cement, thereby improving the durability of the cement.
[0016] On the basis of low-alkali cement, mixed pore-plugging materials are used as the adjustment materials when cement is used. After adding the mixed pore-plugging materials, the cement has enhanced shock resistance and toughness due to the modified plastic powder; gelatin powder can bond cement and form colloids to reduce the production of gaps or holes; the role of the pore-plugging agent is, first, to slowly absorb water in the cement, reduce the outflow of internal water vapor and wait for alkaline substances to the surface of cement products, and second, after absorbing water and swelling, the cement will not lose water even after drying, ensuring the strength of the cement, and further increasing the density of the cement during the later cement curing period. The synergistic effect of these three materials in cement can not only reduce the generation of holes, but also block the evaporation of water vapor, and prevent the cement from having too much water content and curing slowly. DETAILED DESCRIPTION
[0017] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments.
[0018] Therefore, the following detailed description of the embodiments of the present invention is not intended to limit the scope of the invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0019] It should be noted that, in the absence of conflict, the embodiments of the present invention and the features of the embodiments may be combined with each other.
[0020] Embodiment 1: A low-alkali alkali-resistant cement comprises 700-800 parts of limestone, 100-150 parts of riverbed exfoliated clay, 80-100 parts of sandstone, 75-80 parts of modified phosphogypsum, 70-80 parts of bauxite, 60-70 parts of coal gangue, 50-70 parts of tailings, and 30-40 parts of mixed pore-plugging materials; wherein the mixed pore-plugging materials comprise 38-42% of modified plastic powder, 32-35% of gelatin powder, and 25-28% of pore-plugging agent.
[0021] On the basis of general low-alkali cement, alkali-free / low-alkali or acidic riverbed stripping clay is used to replace general clay raw materials, and tailings can be used as iron adjustment material. Bauxite reduces the content of Na2O in cement, which is beneficial to reduce the alkali dissolution of the alkali skeleton in cement and the alkali-silicon reaction of cement, thereby improving the durability of cement. The above raw materials are widely available and inexpensive, which can not only ensure the production of cement, but also reduce the alkalinity in cement.
[0022] Preferably, the pore plugging agent is composed of 80 to 100 parts of a water-absorbing resin, 50 to 55 parts of a rubber, 40 to 45 parts of a water-swellable polyurethane, 10 to 15 parts of a compatibilizer and 1 to 20 parts of a metal ion blocking agent.
[0023] On the basis of low-alkali cement, mixed pore-plugging materials are used as the adjustment materials when cement is used. After adding the mixed pore-plugging materials, the cement has enhanced shock resistance and toughness due to the modified plastic powder; gelatin powder can bond cement and form colloids to reduce the production of gaps or holes; the role of the pore-plugging agent is, first, to slowly absorb water in the cement, reduce the outflow of internal water vapor and wait for alkaline substances to the surface of cement products, and second, after absorbing water and swelling, the cement will not lose water even after drying, ensuring the strength of the cement, and further increasing the density of the cement during the later cement curing period. The synergistic effect of these three materials in cement can not only reduce the generation of holes, but also block the evaporation of water vapor, and prevent the cement from having too much water content and curing slowly, ensuring the normal coagulation and strength of the cement.
[0024] Most water-absorbent resins are made of water-soluble resins through partial crosslinking or saponification. They are generally granular powders, and most of them are not easy to disperse in rubber. The water-absorbent resin is unevenly dispersed in the rubber. When it encounters water, the resin on the surface will be extracted by water, thus affecting the water absorption rate of the product. The water-absorbent resin is used together with water-soluble polyurethane and mixed with rubber to produce water-absorbent rubber with different water absorption expansion rates and mechanical properties. Water-absorbent rubber can also be made by adding other water-absorbent resins to rubber. Water-absorbent resins with high water absorption rate and good strength after water absorption can be selected. Such as partially cross-linked sodium polyacrylate, isobutylene-maleic anhydride copolymer, etc.
[0025] Due to the poor thermodynamic compatibility between rubber materials and water-absorbent resins, they cannot form a good miscible system after mixing. The dispersed phase water-absorbent resins tend to condense together and fall off from the rubber cross-linked network, affecting the water absorption and mechanical properties of the water-swelling rubber. Selecting a suitable compatibilizer can improve the compatibility of rubber materials and water-absorbent resins, thereby improving the water absorption and mechanical properties of the water-swelling rubber. The compatibilizer is a hydrophilic and lipophilic multi-block copolymer with polyethylene oxide blocks.
[0026] Preferably, the water-absorbing resin is a saponified copolymer of vinyl ether and olefin unsaturated carboxylic acid or its derivatives as the main components, or a grafted polymer of polyvinyl alcohol / acrylate. A high molecular electrolyte containing carboxylate is the most suitable water-absorbing resin, which has high strength after water absorption and can also improve the rigidity of the material after water absorption.
[0027] Preferably, the rubber is a 1,3-diene rubber having a crystalline region or a glass transition region of 5% to 50% at room temperature.
[0028] For example, chloroprene rubber has better expansion performance, better elasticity, better processing performance and certain strength than butyl rubber.
[0029] Preferably, the water absorption rate of the water-absorbing resin is 200% to 350% of the medium swelling rate.
[0030] The water absorption rate should be a medium expansion rate to prevent excessive expansion or excessive water absorption, which will have a negative impact on the setting time and setting strength of cement products.
[0031] Preferably, the particle size of the pore plugging agent is between 50 and 100 um.
[0032] In order to overcome the phenomenon of separation of the water-absorbent resin from the rubber substrate, the particle size of the pore-blocking agent should be controlled below 100 um, preferably less than 50 um.
[0033] Preferably, the metal ion blocking agent is a condensed phosphate or aminocarboxylic acid derivative such as ethylenediaminetetraacetic acid and its metal salt. The mixed gel material is also added with 0.5 to 2 parts of an anti-metal corrosion agent.
[0034] This pore plugging agent is used in a humid and harsh environment. Especially when the water contains multivalent metal ions, its water absorption and expansion performance will be affected. In order to avoid this effect, metal ion blocking agents such as condensed phosphates and aminocarboxylic acid derivatives such as ethylenediaminetetraacetic acid and its metal salts can be added to the formula. The amount used is between 1 and 20 parts, depending on the water quality. In some applications that are corrosive to metals, 0.5 to 2 parts of anti-metal corrosion agents should also be added.
[0035] Table 1 The above test data is obtained by drying each test block in a high temperature and humid environment for 28 days. The thickness of each test block is cast and supported according to the construction standard of 200mm, and cut into 50cm*50cm size.
[0036] It can be clearly seen from the above data that the alkali efflorescence of ordinary silicate cement used in test blocks 5, 6, and 7 is the most serious. After adding the mixed pore-plugging material, it will be effectively reduced and the holes will be eliminated, but some will still exist, and the alkali content is relatively high, so the efflorescence phenomenon is serious; for test blocks 8, 9, and 10, low-alkali cement made of blast furnace slag is used, because the metal content increases, it will weaken the mixed pore-plugging material. Blast furnace slag is less hydrated in cement and more holes will be formed after solidification. Therefore, the low-alkali cement cannot be significantly and effectively improved after adding mixed pore-plugging materials; that is, it is necessary to adjust the formula of general low-alkali cement to achieve coordinated cooperation between low-alkali cement and mixed pore-plugging materials. For this product's low-alkali alkali-resistant cement, that is, test blocks 1, 2, 3, and 4, under the premise of reducing alkalinity, it also overcomes its negative impact on the mixed pore-plugging material, and the mixed pore-plugging material can also greatly weaken the existence of holes, promote each other, and achieve the effect of low alkali and alkali-resistant efflorescence.
[0037] Embodiment 2: Based on the above embodiments, this embodiment shows a method for preparing low-alkali alkali-resistant cement, comprising the following steps: S1, take: 750 parts of limestone, 120 parts of riverbed stripping clay, 90 parts of sandstone, 60 parts of tailings, crush, mix and put into kiln for calcination in sequence to obtain clinker; S2, 80 parts of modified phosphogypsum, 75 parts of bauxite, and 65 parts of coal gangue are crushed, mixed with the clinker in S1, and bagged to obtain a semi-finished product; S3. 40% of modified plastic powder, 33% of gelatin powder and 27% of pore plugging agent in 35 parts of mixed filling material are kneaded and crushed at low temperature, then sealed and packaged, and placed in bagged semi-finished products.
[0038] The mixed filling materials and the low-alkali cement product of this product are divided into main materials and auxiliary materials and packaged separately. They should be unpacked before use. This is to prevent the two from mixing and agglomerating due to moisture before use, and to prevent the mixed filling materials from becoming ineffective due to moisture.
[0039] Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments, or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A low-alkali alkali-resistant cement, characterized in that: The low-alkali cement includes 700-800 parts of limestone, 100-150 parts of riverbed exfoliated clay, 80-100 parts of sandstone, 75-80 parts of modified phosphogypsum, 70-80 parts of bauxite, 60-70 parts of coal gangue, 50-70 parts of tailings, and 30-40 parts of mixed plugging materials; among which; The mixed pore plugging material comprises 38-42% of modified plastic powder, 32-35% of gelatin powder and 25-28% of pore plugging agent.
2. The low-alkali alkali-resistant cement according to claim 1, characterized in that: The pore plugging agent comprises 80-100 parts of water-absorbing resin, 50-55 parts of rubber, 40-45 parts of water-swellable polyurethane, 10-15 parts of a compatibilizer and 1-20 parts of a metal ion sealing agent.
3. The low-alkali alkali-resistant cement according to claim 2, characterized in that: The water-absorbing resin is a saponified copolymer mainly composed of vinyl ether and olefin unsaturated carboxylic acid or its derivatives, or a grafted polymer of polyvinyl alcohol / acrylate.
4. The low-alkali alkali-resistant cement according to claim 2, characterized in that: The rubber is a 1,3-diene rubber having a crystallization region or a glass transition region of 5% to 50% at room temperature.
5. The low-alkali alkali-resistant cement according to claim 1, characterized in that: The water absorption rate of the water-absorbing resin is 200% to 350% of the medium swelling rate.
6. The low-alkali alkali-resistant cement according to claim 1, characterized in that: The particle size of the pore plugging agent is between 50 and 100 um.
7. The low-alkali alkali-resistant cement according to claim 1, characterized in that: The metal ion blocking agent is an aminocarboxylic acid derivative such as condensed phosphate or ethylenediaminetetraacetic acid and its metal salt.
8. The low-alkali alkali-resistant cement according to claim 1, characterized in that: The mixed gel material is also added with 0.5 to 2 parts of an anti-metal corrosion agent.
9. The low-alkali alkali-resistant cement according to claim 1, characterized in that: The compatibilizer is a hydrophilic and lipophilic multi-block copolymer of polyethylene oxide blocks.
10. A method for preparing low-alkali alkali-resistant cement, characterized in that: The steps include: S1, take: 750 parts of limestone, 120 parts of riverbed stripping clay, 90 parts of sandstone, 60 parts of tailings, crush, mix and put into kiln for calcination in sequence to obtain clinker; S2, 80 parts of modified phosphogypsum, 75 parts of bauxite, and 65 parts of coal gangue are crushed, mixed with the clinker in S1, and bagged to obtain a semi-finished product; S3. 40% of modified plastic powder, 33% of gelatin powder and 27% of pore plugging agent in 35 parts of mixed filling material are kneaded and crushed at low temperature, then sealed and packaged, and placed in bagged semi-finished products.
